(untitled) (Economics and region, 2020)
A toolkit for regulating the disparities of regional socio-economic development based on fuzzy logic methods, and accounted unstable environment and nonlinear dynamics of disparities, are proposed. The levels of disparities are determined as follows: catastrophic, permissible, and regulated. On the basis of established ranges of factors influencing the disparities, and variables and membership functions for values of disparities levels calculated for each region, fuzzy logical inference is formed – rules of correspondence between factors of influence on disparities and levels of disparities for each region.